2003
DOI: 10.1023/b:pham.0000008037.57884.11
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Biopharmaceutics Classification System: The Central Role of Dose/Solubility Ratio

Abstract: The QBCS provides a basis for compound classification into four explicitly defined drug categories using the fundamental biopharmaceutical properties, permeability, and dose/solubility ratio. Semiquantitative predictions for the extent of absorption are essentially based on these drug properties, which either determine or are strongly related to the in vivo kinetics of drug dissolution and intestinal wall permeation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
12

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(111 citation statements)
references
References 35 publications
3
96
0
12
Order By: Relevance
“…Several information is available on the level of the toxicity of these compounds. Rinaki et al, (2003) have suggested dose/solubility ratio of biopharmaceutics. Acosta et al, (1985) have given an in vitro approach to the study of target organ toxicity of drug and chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Several information is available on the level of the toxicity of these compounds. Rinaki et al, (2003) have suggested dose/solubility ratio of biopharmaceutics. Acosta et al, (1985) have given an in vitro approach to the study of target organ toxicity of drug and chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…8 Acetaminophen (C 8 H 9 NO 2 ) is a crystalline white powder with a bitter taste, is odorless, and has a molecular weight of 151.16. 9,10 About 90% of acetaminophen reacts with 30% sulphate and 60% glucuronide in the liver. These two metabolic pathways can be saturated.…”
Section: Methodsmentioning
confidence: 99%
“…For example, obvious maturation changes are related to the volume increase of luminal fluids, intestinal surface area, and intestinal permeability (12)(13)(14)(15). Administered dose is also fundamentally important, and therefore, there may be a need for a more quantitative, dose-dependent approach to pediatric BCS (16,17). Wu and Benet (18) have proposed an alternative Biopharmaceutics Drug Disposition Classification System which includes the role of metabolism in classifying drugs.…”
Section: Challenges In the Development Of Pediatric Dosage Forms Frommentioning
confidence: 99%